The continuities of German history : nation, religion, and race across the long nineteenth century - Smith, Helmut Walser 1962- (Cambridge University Press, 2008)
The vanishing point of German history -- The mirror turn lamp: senses of the nation before nationalism -- On catastrophic religious violence and national belonging: the Thirty Years War and the massacre of Jews in social memory -- From play to act: anti-Jewish violence in German and European history during the long nineteenth century -- Eliminationist racism -- Conclusion: Continuities in German history